Coordinated 14C and 230Th dating of Kitchen Cave rockshelter, Gambier (Mangareva) Islands, French Polynesia: Comparing 230Th coral dates with Bayesian model ages. (February 2021) - Kirch, Patrick V.; Molle, Guillaume; Niespolo, Elizabeth M.; Sharp, Warren D.
Highlights: Compares high-precision 230 Th coral dates with Bayesian-calibrated radiocarbon dates from a stratigraphic sequence. Demonstrates that 230 Th dating of Acropora coral abraders yields precise and accurate chronological data. Refines the chronology for Kitchen Cave, an important stratified rockshelter in the Mangareva Islands. An early 230 Th date at the base of Kitchen Cave may evidence Polynesian exploration prior to permanent settlement. Abstract: Establishing the timing of human colonization of the eastern Pacific and developing cultural chronologies within the island groups of Eastern Polynesia has relied primarily on 14 C dating. Despite advancements in 14 C dating, however, uncertainties introduced during calibration to calendar ages remain large relative to the tempo of human settlement of the eastern Pacific and ensuing Polynesian cultural development. 230 Th dating of coral abraders, a common artifact in Polynesian archaeological sites, can potentially provide more precise ages. We report a high-precision chronology for the Kitchen Cave rockshelter on Kamaka Island in the Mangareva (Gambier) Islands, based on parallel series of 13 14 C AMS dates on short-lived plant materials and 19 230 Th dates on Acropora coral abraders and non-utilized Acropora coral branches. The 230 Th coral dating results are highly consistent with ages from 14 C dating, except in two cases where corals younger than expected occupied what are most likely intrusive contexts. Moreover, because the 14 C and 230 Th dating techniques are largely independent, obtaining consistent results via the two techniques increases confidence in the resulting chronology. A reliable 230 Th date of 860 ± 5 CE for a coral from the basal layer of the cultural sequence, whose deposition cannot readily be explained by natural processes, raises the possibility of an early Polynesian visit to Kamaka Island some centuries prior to initiation of permanent occupation in the 11th to 13th centuries. These results confirm that 230 Th dating of Acropora branch coral abraders can be applied to other sites in the Pacific with a high degree of confidence.